Cornsilk improves nutrient content and physical characteristics of beef patties - Wan Rosli .W.I,; Nurhanan .A.R,; Solihah .M.A,; Mohsin .S.S.J, (Universiti Kebangsaan Malaysia, 2011)
The nutrient composition, cooking characteristics and sensory properties of beef patties incorporated with various level of cornsilk were studied. The beef patties were formulated with either 2, 4 or 6% of cornsilk. Protein content increased in line with the cornsilk level in both raw and cooked beef patties. Both raw and cooked patties incorporated with 6% cornsilk recorded the highest protein concentration at 17.2 and 23.3%, respectively. Both raw and cooked patties containing 6% cornsilk recorded the lowest concentration of fat at 12.4 and 11.4%, respectively. All cooked patty samples recorded moisture content ranging from 40.42-42.98%. Beef patty formulated with 6% cornsilk recorded the highest cooking yield at 80.13% compared to other treatments. The addition of cornsilk did not change the sensory properties and consumer acceptability of cornsilk-based beef patties. Cornsilk fibre was effective in improving cooking yield, moisture and fat retention and enhancing texture of beef patties.